Little Panguingue Creek: A c. 9600-Year-Old Prehistoric Knapping Workshop in the Nenana Valley, Central Alaska*. (2nd January 2019) - Gómez Coutouly, Yan Axel; Graf, Kelly E.; Gore, Angela K.; Goebel, Ted
ABSTRACT: The Nenana Valley near Healy, Alaska, has been the site of many decades of prehistoric archaeological research focused on the late Pleistocene and early Holocene records. New research at the Little Panguingue Creek (LPC) site (HEA-038) provides us with important information about Pleistocene–Holocene human activities in the Nenana Valley foothills. This multi-component site is located on a Healy-aged glacial-outwash terrace, overlooking LPC. A new multi-year excavation program, begun in 2015, revealed a c. 9600 cal yr BP knapping workshop (hammerstones, cores, preforms, cortical spalls, tools, debitage, etc.) with a major microblade component dating from the final phase of the Denali complex, along with an older component dating to c. 11, 150 cal yr BP. On-going research at the site will further our understanding of human technological, subsistence, and settlement organization in the Nenana Valley (and beyond) during the Pleistocene/Holocene transition. Here we present preliminary results of work accomplished so far.